Does regulation hold the key to optimizing lipopeptide production in Pseudomonas for biotechnology? - Zhou, Lu; Höfte, Monica; Hennessy, Rosanna C. (Frontiers in Bioengineering and Biotechnology, 2024)
Lipopeptides (LPs) produced by Pseudomonas spp. are specialized metabolites with diverse structures and functions, including powerful biosurfactant and antimicrobial properties. Despite their enormous potential in environmental and industrial biotechnology, low yield and high production cost limit their practical use. While genome mining and functional genomics have identified a multitude of LP biosynthetic gene clusters, the regulatory mechanisms underlying their biosynthesis remain poorly understood. We propose that regulation holds the key to unlocking LP production in Pseudomonas for biotechnology. In this review, we summarize the structure and function of Pseudomonas-derived LPs and describe the molecular basis for their biosynthesis and regulation. We examine the global and specific regulator-driven mechanisms controlling LP synthesis including the influence of environmental signals.Understanding LP regulation is key to modulating production of these valuable compounds, both quantitatively and qualitatively, for industrial and environmental biotechnology.